Empowerment of Village Owned Enterprises through E-Commerce Information Technology in Increasing the Economy of Sipodeceng Village Communities - Razak, Muhammad Rais Rahmat; Mursalat, Aksal; Sellang, Kamaruddin; Syarifuddin, Rifni Nikmat; Ramadhan, Muhammad Rohady; Irwan, Muh.; Asra, Reza; Bibin, Muhammad; Said, Sunandar; Andreani, Andi Riska; Latif, Adam; B, Sofyan; Syam, Syaiful Bahri; Aksan, Muhammad (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: This activity aims to increase the role of Bumdes Padaidi Sipodeceng through e-commerce information technology based on the Bumdes Sipodeceng Store application in improving the economy of the people of Sipodeceng Village. Contribution: This activity improves the welfare of the people of Sipodeceng Village through e-commerce information technology. Method: The method of this activity includes Socialization of the implementation of activities, Counseling by explaining the e-commerce information technology marketing model (BUMDES Sipodeceng Store), training and mentoring the use of information technology for BUMDES partner groups, carrying out assistance, as well as monitoring and evaluation. Results: Training and mentoring activities based on pre-test and post-test data analysis have positive implications for 3 parameters: knowledge from 42.14 to 89.14%, skills from 35.9% to 90.12%, and motivation from 63.2% to 93 .2%. From these data, an analysis of the effectiveness of these 3 parameters is carried out, the values of which are knowledge at 81%, skills at 85%, and motivation at 79%. These three numbers indicate that community service activities are effective because the value is above 50%. Conclusion: From these activities, it can be concluded that e-commerce information technology at BUMDES Padaidi Sipodeceng is still very much needed to increase the role of BUMDES in community empowerment.